Analysis of gas condensate and its different fractions of Bibiyana gas field to produce valuable products - Sujan, SMA; Jamal, MS; Hossain, M; Khanam, M; Ismail, M (Bangladesh Journal of Scientific and Industrial Research, 2015)
Physicochemical characteristics of raw gas condensate from Bibiyana gas field, commercial motor spirit, kerosene and diesel fuel as well as products obtained from gas condensate were determined. Experiments were carried out to take apart motor spirit, kerosene and diesel from gas condensate based on boiling ranges. The analysis revealed that collected gas condensate contains more than 50% is motor spirit (regular octane/petrol) in the boiling range of 21-1450C, 23% is kerosene in the boiling range of 140-2210C and 24-25% is diesel in the boiling range of 178-3350C. Remaining 2-3% is found as residue and system loss. The characteristics of different fractions (Motor spirit, Kerosene & Diesel) obtained from condensate are very comparable to commercial products (collected from nearby fuel pump station supplied by Meghna petroleum) and BSTI standard except two properties of petrol (octane number and sulfur content). The octane number of motor spirit is increased by adding 5% of supper octane or ethanol or MTBE. Bangladesh J. Sci. Ind. Res. 50(1), 59-64, 2015